2020
DOI: 10.1177/0091552120964873
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Sense of Belonging, Socioacademic Integrative Moments, and Learning Communities Related to ELs’ Persistence Based on Reenrollment Decisions in Community Colleges

Abstract: Objective: The objective of this study was to create a model of English learners’ (ELs) persistence based on theory and empirical research. Findings from this research informs community college educators in helping ELs persist and guide future research regarding this important student population. Method: We examined ELs’ persistence using structural equation modeling (SEM) based on data from the Community College Survey of Student Engagement (CCSSE) among a U.S. national sample of 6,872 ELs. SEM was informed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…In addition, the findings are also congruent to the related literature and studies from (Abdelmalak, 2015;Abubakar & Garko, n.d.;Bâcă, 2020;Garza et al, 2021;IŞIKLI & Tarakcioglu, 2017;Murdock & Williams, 2011;Naji et al, 2019;Spiridon et al, 2020) which, in one way or another, all recommended the idea of building a virtual community of learners for an enhanced and maximized educational experience.…”
Section: Findings Swot Analysis Results Of Wattpad E-communitysupporting
confidence: 84%
“…In addition, the findings are also congruent to the related literature and studies from (Abdelmalak, 2015;Abubakar & Garko, n.d.;Bâcă, 2020;Garza et al, 2021;IŞIKLI & Tarakcioglu, 2017;Murdock & Williams, 2011;Naji et al, 2019;Spiridon et al, 2020) which, in one way or another, all recommended the idea of building a virtual community of learners for an enhanced and maximized educational experience.…”
Section: Findings Swot Analysis Results Of Wattpad E-communitysupporting
confidence: 84%
“…Smith (2015) found that learning communities are useful in getting students to study together and this leads to higher academic performance. In another study, Garza et al (2021) found that the use of these learning communities assisted international students to socialize with one another and learn from each other. Interactions among students during meetings within these learning communities are thought to be beneficial in terms of academic persistence (Fergy et al, 2011).…”
Section: Learning Communitiesmentioning
confidence: 99%
“…It has been observed that the perceived social support and the interpersonal relationships that students establish with their peers, teachers and members of the university campus are fundamental aspects to develop a sense of belonging [40][41][42][43][44], an aspect inversely related to the dropout intention. This is because social support and positive interactions are essential for the development of a sense of belonging in university students [40,45]. The support of peers and parents has also shown to influence the sense of belonging to the institution and has been linked to a greater institutional engagement [46].…”
Section: Support and Perceived Social Isolationmentioning
confidence: 99%
“…The sense of belonging is defined as the perception of membership or feeling part of the educational organization (study program) in which they study [61]. Feeling belonging to the career implies that the student feels valuable and respected in their own educational program [40,[43][44][45][62][63][64][65][66]. It implies a perceived bond between the student and others, which unites them to a group or community, even in difficult moments or in the face of challenges [67], and the impulse that mobilizes them to create and maintain meaningful and lasting interpersonal relationships [68].…”
Section: Sence Of Belongingmentioning
confidence: 99%
See 1 more Smart Citation